Long-term follow up after percutaneous PFO closure. Does baseline PFO anatomy affect the long term procedural result and the severity of residual shunt?. (14th October 2021) - Katsianos, E; Oikonomou, E; Kalogeras, K; Manousaki, A; Moldovan, C; Aznaouridis, K; Katsarou, O; Kalantzis, C; Siasos, G; Vavouranakis, E
Abstract: Background: Patent foramen ovale (PFO) has been increasingly identified as a cause for left circulation thromboembolism. The risk is even higher in patients with specific anatomic features, like atrial septal aneurysm (ASA), prominent Eustachian valve and Chiari network. Transcranial Doppler with detection of high intensity signals (HITS), after injection of agitated saline, contributes to diagnosis and follow up of patients with PFO. Percutaneous PFO closure is a well-established therapy, if indicated. It remains though unclear, whether the baseline anatomy has an impact on the long-term procedural result. Purpose: To investigate if there was a difference in the number of detected HITS after bubble test in patients with baseline high-risk anatomy in comparison to patients without complex features at least 1 year post-procedurally. Methods: Consecutive patients, who underwent percutaneous closure, were investigated at least one year post implantation. Patients were classified in two groups according to presence or not of high-risk baseline anatomy. Every patient underwent transcranial Doppler with bubble test with agitated saline at rest and after Valsalva maneuver with documentation of HITS up to 60 sec after the straining maneuver. Results: 38 consecutive patients were included (42% men) with mean age 51±12 years and a mean follow-up period of 9±3 years. At baseline 14 patients (37%) had high risk anatomy (7 patients with ASA, 3 with Chiari network and 4 with prominent eustachian valve). There was no difference between the two groups in the mean age (no high-risk: 53±11 years vs high-risk: 48±13 years, p=0.22), in the duration of follow-up period (no high-risk: 9±3 years vs high-risk: 10±2 years, p=0.66) and in other risk factors (Table). The number of documented HITS after Valsalva maneuver was significantly higher in patients with high-risk morphological features [7.50 (10.25–1.50) vs. 0.00 (0.00–3.75), p=0.003] (Figure, panel A). [bo2] Among patients with high risk features six were on prolonged antiplatelet therapy with either aspirin or P2Y12-inhibitor. Patients with high-risk features on prolonged therapy had significant lower HITS [1.00 (0.00–3.25)] compared to patients with high risk features and no prolonged antiplatelet therapy [10.00 (8.25–13.25)] (p=0.008) (Figure, panel B). Recurrent cerebrovascular accidents were similar in both groups (2 events with high-risk anatomy and 1 event without). No patient regardless of PFO morphology and antiplatelet strategy showed a significant right to left shunt (>30 HITS according to Spencer scale) Conclusion: Percutaneous PFO closure is an effective therapy for paradoxical left circulation thromboembolism. Patients with high-risk anatomy may show an increased prevalence of residual, though clinically irrelevant shunt and may require a stricter follow-up. Prolonged antiplatelet therapy may reduce the number of detected microbubbles. Randomized data are required to evaluate this hypothesis. Funding Acknowledgement: Type of funding sources: None.